Causes and Consequences of a Variant Strain of Phaeobacter inhibens With Reduced Competition - Majzoub, Marwan E.; McElroy, Kerensa; Maczka, Michael; Thomas, Torsten; Egan, Suhelen (Frontiers in Microbiology, 2018)
Phaeobacter inhibens 2.10 is an effective biofilm former and colonizer of marine surfaces and has the ability to outcompete other microbiota. During biofilm dispersal P. inhibens 2.10 produces heritable phenotypic variants, including those that have a reduced ability to inhibit the co-occurring bacterium Pseudoalteromonas tunicata. However the genetic changes that underpin the phenotypic variation and what the ecological consequences are for variants within the population are unclear. To answer these questions we sequenced the genomes of strain NCV12a1, a biofilm variant of P. inhibens 2.10 with reduced inhibitory activity and the P. inhibens 2.10 WT parental strain. Genome wide analysis revealed point mutations in genes involved in synthesis of the antibacterial compound tropodithietic acid (TDA) and indirectly in extracellular polymeric substances (EPS) production. However confocal laser scanning microscopy analyses found little differences in biofilm growth between P. inhibens 2.10 WT (parental) and NCV12a1. P. inhibens NCV12a1 was also not outcompeted in co-cultured biofilms with P. tunicata, despite its reduced inhibitory activity, rather these biofilms were thicker than those produced when the WT strain was co-cultured with P. tunicata. Notably, dispersal populations from biofilms of P. inhibens NCV12a1 had a higher proportion of WT-like morphotypes when co-cultured with P. tunicata. These observations may explain why the otherwise non-inhibiting variant persists in the presence of a natural competitor, adding to our understanding of the relative importance of genetic diversification in microbial biofilms.